THE ARRANGEMENT OF ECO-SETTLEMENT AROUND PUSPA AGRO AND INDUSTRY IN TAMAN SUBDISTRICT SIDOARJO - Fakhurin K. Noviabahari; Happy Ratna Santosa; Ispurwono Soemarno (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2012)
The presence of national trade center and industry in an area could provoke urbanization. As it is known that the problem of urbanization always leads to an increased demand of housing. Similarly, the development of Puspa Agro (AgrobisTrade Center) and industry in Taman Sub-District, Sidoarjo. If the surroundingsettlements grow out of control, the region will eventually face problems like thegrowth of marginal areas. Besides the agricultural sector could also be threatened because of diminishing land area. The purpose of this study is to determine the extent of settlement’s development in Desa Sadang and Jemundo before and after the development of Puspa Agro and industry. Then, we look for the proper arrangement’s concepts of eco-settlement to be applied at the sites. Method used in this study is qualitative descriptive with naturalistic paradigm. This is to obtain factual and accurate description of the changes in settlement’s condition before and after the development of Puspa Agro and industry. Primary data was collected by interview, observation, and physical measurement. The result of this study shows that the settlement’s development is still in the standard of housing and settlements. Also discovered the right concept of eco-settlement’s arrangement to be applied around the trade center and industry.